Comparative proteomics of the two T. brucei PABPs suggests that PABP2 controls bulk mRNA. - Martin Zoltner; Nina Krienitz; Mark C Field; Susanne Kramer (PLoS Neglected Tropical Diseases, 2018)
Poly(A)-binding proteins (PABPs) regulate mRNA fate by controlling stability and translation through interactions with both the poly(A) tail and eIF4F complex. Many organisms have several paralogs of PABPs and eIF4F complex components and it is likely that different eIF4F/PABP complex combinations regulate distinct sets of mRNAs. Trypanosomes have five eIF4G paralogs, six of eIF4E and two PABPs, PABP1 and PABP2. Under starvation, polysomes dissociate and the majority of mRNAs, most translation initiation factors and PABP2 reversibly localise to starvation stress granules. To understand this more broadly we identified a protein interaction cohort for both T. brucei PABPs by cryo-mill/affinity purification-mass spectrometry. PABP1 very specifically interacts with the previously identified interactors eIF4E4 and eIF4G3 and few others. In contrast PABP2 is promiscuous, with a larger set of interactors including most translation initiation factors and most prominently eIF4G1, with its two partners TbG1-IP and TbG1-IP2. Only RBP23 was specific to PABP1, whilst 14 RNA-binding proteins were exclusively immunoprecipitated with PABP2. Significantly, PABP1 and associated proteins are largely excluded from starvation stress granules, but PABP2 and most interactors translocate to granules on starvation. We suggest that PABP1 regulates a small subpopulation of mainly small-sized mRNAs, as it interacts with a small and distinct set of proteins unable to enter the dominant pathway into starvation stress granules and localises preferentially to a subfraction of small polysomes. By contrast PABP2 likely regulates bulk mRNA translation, as it interacts with a wide range of proteins, enters stress granules and distributes over the full range of polysomes.